2021
DOI: 10.1101/2021.11.06.21265967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity of COVID-19 vaccines in patients with haematological malignancy: A systematic review and meta-analysis

Abstract: The objectives of this study were to assess the immunogenicity and safety of COVID-19 vaccines in patients with haematological malignancy. A systematic review and meta-analysis of clinical studies of immune responses to COVID-19 vaccination stratified by underlying malignancy and published from 1 January 2021 to 31 August 2021 was conducted using MEDLINE, EMBASE and CENTRAL. Primary outcome was the rate of seropositivity following 2 doses of COVID-19 vaccine with rates of seropositivity following 1 dose, rates… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 74 publications
2
11
0
2
Order By: Relevance
“…Our data, even though based on a small patient cohort, highlight that CLL patients have a very low rate of response to SARS-CoV-2 immunization and a very high risk for severe disease and death due to COVID-19, according to what was previously reported in literature so far [ 5 , 6 , 15 , 16 , 17 , 18 ]. In particular, patients on active treatment with target therapies and anti-CD20 MoAb are at high risk for low rate of response [ 8 , 9 , 19 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our data, even though based on a small patient cohort, highlight that CLL patients have a very low rate of response to SARS-CoV-2 immunization and a very high risk for severe disease and death due to COVID-19, according to what was previously reported in literature so far [ 5 , 6 , 15 , 16 , 17 , 18 ]. In particular, patients on active treatment with target therapies and anti-CD20 MoAb are at high risk for low rate of response [ 8 , 9 , 19 ].…”
Section: Discussionsupporting
confidence: 84%
“…Patients with CLL are reported to have high rates of both severe disease and death for COVID-19 [ 3 , 4 ]. In addition, poor serological response to the SARS-CoV-2 vaccines in those patients has already been described [ 2 , 5 ]. However, immunocompromised patients were excluded from early trials of COVID-19 immunization.…”
Section: Introductionmentioning
confidence: 99%
“…We also found there were no non responders to Covishield which is in contrast to other studies which showed the presence of non responders in persons with Immune Mediated Inflammatory disease (IMId) and persons with hematological malignancies. 8,9 In our study, we found 9.5% of the study participants did not have protective antibody titers 6 months following 2 doses of Covishield. Other studies have also documented waning immunity following 2 doses of COVId-19 vaccines they have not clearly stated the duration after which immune waning occurs.…”
Section: Discussionmentioning
confidence: 49%
“…Letztere kann mit einer erheblichen MorbiditĂ€t und LetalitĂ€t einhergehen. Eine SARS-CoV-2-Infektion in der immunsupprimierten Population unterscheidet sich von Infektionen bei Gesunden durch eine erhöhte MorbiditĂ€t und LetalitĂ€t sowie ein erhöhtes Ansteckungsrisiko, unter anderem durch suboptimale impfinduzierte Immunantwort sowie protrahierte VerlĂ€ufe mit persistierendem Virusnachweis 18 19 .…”
Section: Virale Infektionenunclassified
“…WĂ€hrend bei Immunkompetenten in vielen FĂ€llen Antikörpertiter als Schutzsurrogat verwendet werden, ist dies bei Immunsupprimierten aufgrund von B-Zell-Depletion durch Therapie und/oder Grunderkrankung nur bedingt oder gar nicht möglich. Hier scheint die T-Zell-Antwort eine entsprechend grĂ¶ĂŸere Rolle zu spielen, wie nicht zuletzt bei COVID-19-Impfungen gezeigt wurde 18 . Die zellulĂ€re Immunantwort bietet insbesondere Schutz vor schweren KrankheitsverlĂ€ufen, spielt aber bei der Abwehr der initialen Infektion im Gegensatz zu Antikörpern nur eine geringe Rolle.…”
Section: Impfungenunclassified